Pemanfaatan Bahan Organik sebagai Pembawa untuk Peningkatan Kepadatan Populasi Trichoderma viride pada Rizosfir pisang dan Pengaruhnya terhadap Penyakit Layu Fusarium - . Nurbailis; . Martinius (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
The aims of the research were to determine the best organic matter as carrier for growth and increasing the density of Trichoderma viride strain TV-T1sk (TV-T1sk) and its influence on Fusarium wilt disease development on banana seedling. This research consisted of two experiments, i.e. (1). Growth testing of TV-T1sk in various organic matter, (2). Various organic matter testing for increasing the density of TV-T1sk in banana rhizosphere and its influence on Fusarium wilt desease development. The treatments were various organic matter, namely rice straw, sugar cane pulp, rice bran+banana plant waste, hull of rice+sugar cane pulp and rice. The variables observed were density and viability of conidia on various organic matter. Propagule density after introduction to banana rhizosphere was determined by observing TV-T1sk propagul from the rizosphere of banana seedling. The influence of density on Fusarium wilt disease development was determined by incubation period, the percentage of symptomized leaves and the intensity of corm damage. The results showed that both sugar cane pulp and rice were the best organic matter for increasing the growth and the density of TV-T1sk after introduction to banana rhizosphere. The density of TV-T1sk propagule on banana rhizophere influenced the development of Fusarium wilt disease.